2002
DOI: 10.1021/jp0128168
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study on the (OCS)2·CO2van der Waals Trimers

Abstract: Ab initio calculations [MP2, MP4SDTQ, and QCISD(T)] using different basis sets [6-31G(d,p), cc-pVXZ (X ) D, T, Q), and aug-cc-pVDZ] were carried out to study the (OCS) 2 ‚CO 2 van der Waals trimers. Three barrel-like structures [C 1 (two) and C 2 symmetry] and three planar (C s ) structures were located on the potential energy surface. Their CBS-MP2/cc-pVXZ (X ) D, T, Q) stabilization energies are 1760 (C 1 ), 1514 (C 2 ), 1660 (C 1 ), 1325 (C s ), 1556 (C s ), and 1398 (C s ) cm -1 , respectively. The most st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 61 publications
6
29
1
Order By: Relevance
“…It is interesting to observe that the CPR correction changes the activation energy in the correct direction but it is too big, probably as a consequence of the overcorrection associated with the CP algorithm to correct for BSSE at the correlated level. 33 As concluded in recent studies 34,35 where the CP values are compared with those arising from the application of BSSE-free methods, the real values must lie somewhere between the NCP and CPR estimates.…”
Section: Influence Of Bsse On Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to observe that the CPR correction changes the activation energy in the correct direction but it is too big, probably as a consequence of the overcorrection associated with the CP algorithm to correct for BSSE at the correlated level. 33 As concluded in recent studies 34,35 where the CP values are compared with those arising from the application of BSSE-free methods, the real values must lie somewhere between the NCP and CPR estimates.…”
Section: Influence Of Bsse On Resultsmentioning
confidence: 99%
“…A number of authors 33 noticed overcorrections when the CP method is applied at the correlated levels. Further, recent works 34,35 where BSSE-free techniques, like the symmetryadapted perturbation theory (SAPT) 36 or complete basis set (CBS) 37 extrapolations, are employed seem to provide arguments confirming that apparent limitation of the CP method. However, in any case, experience suggests that the CP correction is useful to provide upper limits for the interaction energies.…”
Section: Methodsmentioning
confidence: 99%
“…However, the use of this method is polemic since several authors have reported that it overestimates the BSSE (see refs. [36][37][38][39][40][41][42][43][44] and references therein).…”
Section: On the Basis Set Superposition Error (Bsse) Dilemmamentioning
confidence: 99%
“…So there can be little doubt that isomer a is the lowest energy ground state form of OCS-CO 2 , in agreement with ab initio results. 3 Interestingly, however, we observed that the 2055.7 cm −1 band ͑isomer b͒ seemed to be stronger than the 2066.1 cm −1 band ͑isomer a͒ by a factor of approximately 1.5-2.0 when helium was the carrier. Because of the variation of laser power and other experimental parameters, this intensity ratio is subject to large uncertainties.…”
Section: Discussionmentioning
confidence: 60%
“…These two isomers agree fairly well with the predicted structures from an ab initio calculation by Valdés and Sordo. 3 Following them, we label the two forms as isomers a ͑the original one͒ 1 and b ͑the new one observed here͒. In our experiment, the band of isomer b actually appears to be stronger than that of the isomer a, but the calculations and our experimental test both suggest that isomer a is the lowest energy form.…”
Section: Introductionmentioning
confidence: 70%